Phytochemicals From Vicia faba Beans as Ligands of the Aryl Hydrocarbon Receptor to Regulate Autoimmune Diseases - Méndez-López, Luis Fernando; Sosa de León, Deisy; López-Cabanillas Lomelí, Manuel; González-Martínez, Blanca Edelia; Vázquez-Rodríguez, Jesús Alberto (Frontiers in Nutrition, 2022)
Legumes are associated with gut health benefits, and increasing evidence indicates that their consumption reduces the risk of chronic diseases that include autoimmunity. Beans are rich sources of compounds with health-promoting effects, and recent metabolomic approaches have enabled the comprehensive characterization of the chemical composition of Vicia faba L. This article reviewed whether the phytocompounds in broad beans might modulate the aryl hydrocarbon receptor (AhR), which plays an essential role in autoantigen tolerance as a potential dietary strategy for autoimmune disease management. Therefore, thirty molecules present in Vicia faba of the chemical classes of flavonoids, chalcones, stilbenes, jasmonates, alkaloids, and amino acids, and either a human- or microbiome-derived product of biotransformation, retrieved from the literature or predicted in silico were evaluated by docking for affinity against the ligand-binding domain of AhR. Most analyzed compounds showed high affinity even after their metabolism which indicate that some AhR modulators remain active despite several steps in their biotransformation. Hence, our results suggest that in similitude with the gut metabolism of the tryptophan, phytocompounds mainly polyphenols also lead to metabolites that induce the AhR pathway. Furthermore, wyerone acid, wyerone epoxide, jasmonic acid, stizolamine, vicine, and convicine and their metabolite derivatives are reported for the first time as potential AhR ligands. Overall, chronic consumption of phytochemicals in Vicia faba L. and their gut biotransformation may protect against autoimmune disease pathogenesis by AhR modulation.